Metodologia de posicionamento de unidades estacionárias de produção e rotas de dutos submarinos na produção de petróleo offshore - Santos, Thiago Duarte Fonseca dos (2018)
This work developed methodologies and formulations for automated evaluation of the positioning of stationary FPSO production unit with mooring spread anchorage system, considering the constraints and requirements that must be evaluated to ensure the technical feasibility of the lease. In addition, a methodology was developed to determine the interconnection sequence of the wells, algorithm for deviation of obstacles, formulation for cost estimation and logic for the modeling of subsea architectures. With all these methodologies and formulation, through exhaustive search, with region of interest and determined step, to compare the various viable positions in the search of the optimal position for a given scenario, as well as, allow the confrontation of several models with varied subsea architectures. The results of the case studies proved the efficiency of the methodologies and the adherence of the results, having potential of application in real projects of the oil and gas production development industry.